Artificial Intelligence and Criminal Liability: Reassessing Mens Rea in the Indonesian and Global Contexts - Dita Aprianti; Padrisan Jamba (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-Undangan dan Ekonomi Islam, 2026)
Ideally, criminal law ensures legal certainty and justice through the concept of mens rea, which links the offender’s mental fault to the criminal act. In reality, however, the rapid development of artificial intelligence demonstrates that AI systems may cause harmful consequences without intent, awareness, or volition comparable to those of humans, thereby challenging the anthropocentric framework of mens rea. This condition gives rise to a responsibility gap, particularly in Indonesia, where comprehensive legal regulation on AI remains limited. This study aims to re-examine the concept of mens rea in criminal law by assessing its relevance to the use of AI in both global and Indonesian contexts, while exploring the possibility of reconstructing a more adaptive model of criminal liability. This article employs library-based research with a qualitative normative approach, analyzing statutory regulations, doctrines of modern criminal law, and literature on Islamic law. The findings indicate that mens rea is not abandoned but requires reconstruction through systemic, risk-based approaches and corporate criminal liability, which are consistent with the principle of maslahah and harm prevention in Islamic law, in order to safeguard substantive justice in the digital era.